Correlation of Short Chain Fatty Acid Levels in Patients Non-Alcoholic Fatty Liver Disease with Obesity - Mustika, Syifa; Safira, Zahra; Rosandi, Rulli; ., Supriono; Wibowo, Bogi Pratomo; Muthiah, Mark (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2025)
Background: NAFLD has the potential to develop into severe diseases like NASH and cirrhosis and is often linked to obesity, although it can also occur in non-obese individuals, complicating diagnosis. SCFAs, produced by intestinal bacteria through the fermentation of dietary fibers, are essential for metabolic health and may influence liver fat and weight regulation. The purpose of this study was to explore the connection between SCFA levels and the severity of NAFLD, including liver fibrosis, in individuals both with and without obesity.Methods: A cross-sectional investigation of 16 NAFLD patients with obesity and 11 without, with stool samples analyzed for SCFA via gas chromatography. Obesity was defined by abdominal circumference. Data were analyzed using Spearman’s correlation, Eta’s correlation, and Pearson’s test.Results: Levels of SCFAs, including butyrate, propionate, and acetate, were significantly correlated in both obese and non-obese individuals diagnosed with NAFLD (r=0.618, p=0.001; p=0.019; p=0.037; p=0.012). Obesity was found to be positively associated with the severity of NAFLD (r=0.582, p=0.001). However, obesity did not exhibit a statistically significant connection with liver fibrosis (p = 0.351).Conclusion: Obese NAFLD patients exhibited decreased SCFA levels compared to non-obese individuals. Central obesity was linked to NAFLD severity but not fibrosis progression. SCFAs and obesity are crucial in the pathogenesis of NAFLD.Keywords: Central obesity, gut microbiota, NAFLD, SCFA